1992
DOI: 10.1073/pnas.89.11.4996
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the human CYP11B2 (aldosterone synthase) gene causing corticosterone methyloxidase II deficiency.

Abstract: Corticosterone methyloxidase H (CMO-II) deficiency is an autosomal recessive disorder of aldosterone biosynthesis, characterized by an elevated ratio of 18-hydroxycorticosterone to aldosterone in serum. It is genetically linked to the CYPiIB) and CYP11B2 genes that, respectively, encode two cytochrome P450 isozymes, P45OXIB1 and P450XIB2. Whereas P45OXIB1 only catalyzes hydroxylation at position 1113 of 11-deoxycorticosterone and 11-deoxycortisol, P450XIB2 catalyzes the synthesis of aldosterone from deoxycorti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
90
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(97 citation statements)
references
References 34 publications
7
90
0
Order By: Relevance
“…As a mirror image, patients with inborn errors in the biosynthesis of aldosterone present with salt wasting, severe hypotension, and a decreased distal tubular K + and H + secretion. Wellcharacterised syndromes include homozygous loss of aldosterone synthase activity (the actual mirror image of GRA) or 21-hydroxylase activity (Mitsuuchi et al 1992;Pascoe et al 1992b;Bongiovanni and Root 1963;Armor et al 1988).…”
Section: Monogenic Hypotensionmentioning
confidence: 99%
“…As a mirror image, patients with inborn errors in the biosynthesis of aldosterone present with salt wasting, severe hypotension, and a decreased distal tubular K + and H + secretion. Wellcharacterised syndromes include homozygous loss of aldosterone synthase activity (the actual mirror image of GRA) or 21-hydroxylase activity (Mitsuuchi et al 1992;Pascoe et al 1992b;Bongiovanni and Root 1963;Armor et al 1988).…”
Section: Monogenic Hypotensionmentioning
confidence: 99%
“…Within the small number of patients with congenital hypoaldosteronism due to aldosterone synthase deficiency, patients with CMO deficiency type I appear to have the more severely decreased enzyme activity of P450c11Aldo compared with those with CMO deficiency type II (8)(9)(10)(11)(12)(13). The stop mutation in exon 4 which was identified in the two brothers might explain the biochemical phenotype, because the predicted enzyme has lost the five terminal exons encoding for several a-helices and b-strands which contain important residues for proton transfer, accessory protein binding, haem binding and substrate binding (19).…”
Section: European Journal Of Endocrinology (1998) 139mentioning
confidence: 99%
“…Both disorders are characterised clinically by salt-wasting, failure to thrive and growth retardation. Molecular genetic analysis of the genomic DNA from CMO deficiency type I and II patients led to the identification of mutations in the CYP11B2 gene (8)(9)(10)(11)(12)(13). However, one study showed no CYP11B2 gene mutations in a patient with CMO deficiency type II (14).…”
Section: Introductionmentioning
confidence: 99%
“…The possible role of aldosterone was further evidenced by the finding that loss-and gainof function due to distinct gene variants of CYP11B2 may predispose for or protect from preeclampsia, respectively. In fact, the V386A variant of CYP11B2 gene, which causes a deficiency in the rate-limiting step of aldosterone synthesis, the 18-hydroxycorticosterone methyl oxidase activity [30], was observed solely in a subgroup of preeclamptic women, but never in normal pregnant women [35]. In contrast, the gain of function variants of the CYP11B2 gene in the SF-1 and Int2 (C) sites, which have been shown to be associated with hypertension in non-pregnant subjects [26], apparently reduce the risk of developing preeclampsia [8].…”
Section: Introductionmentioning
confidence: 99%